Pengaruh Fear Of Missing Out (Fomo) terhadap Pembelian Implusif Online Food Delivery pada Generasi Z - Asyifa, Haura Ardella; Hidayah, Khairunnisa; Haryanto, Handrix Chris (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
This study aims to see whether there is an influence between fear of missing out (FoMO) on impulsive purchases of online food delivery in generation Z. This research method uses a quantitative approach by looking at the causal relationship of a variable with 200 respondents with a birth range of 1997-2012, namely generation Z, who likes making purchases via online food delivery and often follows trends on social media, especially food trends, is a participant in this research. The data collection technique used was a questionnaire via Google Form and distributed online. The sampling technique used is non-probability sampling. This study use two scales: the fear of missing out (FoMO) scale and the impulsive buying scale. The results of this research show that there is a significant positive influence (p < 0.05) between fear of missing out on impulsive purchases of online food delivery in generation Z. This means that the higher a person's FoMO value, the higher the impulse purchasing value. The results of this study can be a consideration for Generation Z individuals so that they are not easily influenced by trends on social media so that they can reduce impulse buying, especially through online food delivery.